Back Cover: In Vivo Synthesis of Polyhydroxylated Compounds from a "Hidden Reservoir" of Toxic Aldehyde Species (ChemCatChem 15/2017). Issue 15 (9th August 2017) - Bayer, Thomas; Milker, Sofia; Wiesinger, Thomas; Winkler, Margit; Mihovilovic, Marko D.; Rudroff, Florian
Abstract : The Cover shows a biochemical cell factory ( Escherichia coli ) for the synthesis of chiral polyhydroxylated compounds via an artificial enzyme cascade.In their Communication, T. Bayer et al. presented a rational approach for tuning the concentration of toxic aldehyde intermediates in living cells. By combining an alcohol dehydrogenase and a carboxylic acid reductase, the redox equilibrium between alcohol, aldehyde and carboxylic acid species can be adjusted, thus maintaining the aldehyde concentration in a 'hidden reservoir' and therefore below the toxicity level, yet freely available for subsequent aldolase mediated reaction. More information can be found in the Communication by T. Bayer et al. onpage 2919 in Issue 15, 2017 (DOI:10.1002/cctc.201700469 ).